Completeness of handwritten preanaesthetic records at two veterinary referral institutions. (March 2018) - Mair, Alastair; Mathis, Alessandra
Abstract: Objective: To retrospectively analyse handwritten preanaesthetic records for completeness at two veterinary referral institutions: a university veterinary teaching hospital and a private veterinary referral hospital. To evaluate if emergency records were less complete compared with non-emergency records. Animal or Animal Population Two hundred and fifty preanaesthetic records at each referral institution. Materials and Methods: Handwritten preanaesthetic records were analysed for completeness. Data was described as complete or incomplete. In order to be classified as complete information had to be present, legible and correct. Sections of the preanaesthetic record analysed included the date, anaesthetist, clinician, presenting problem, procedure, time food withheld, temperature, pulse rate (PR), respiratory rate ( f R), American Society of Anesthesiologists-Physical Status Classification (ASA-PSC), premedication drug name, premedication drug dose, premedication route of administration, premedication time, effect of premedication, induction drug name, induction drug dose, induction time, induction quality, maintenance anaesthetic agent, endotracheal tube (ET) diameter, anaesthetic breathing system and monitoring equipment. Results: At both referral institutions 250 records were analysed. Completeness of data was generally poor, however, several differences did exist. Completion rates were generally higher at the university veterinary teaching hospital. A mix of structured and unstructured (requiring free text) data fields were poorly complete. Emergency records were significantly less complete with respect to: Time food withheld ( p = 0.006) and Temperature ( p = 0.0275). Conclusions: Differences observed may be due to anaesthetic record design, anaesthetic caseload, case discussion, education or quality assurance programmes. Clinical relevance Increased emphasis on education and implementation of quality assurance programmes should be considered in order to improve completeness of preanaesthetic records.